Theoretical Studies on Structure of the Soil Contaminating Phenylurea Herbicides - VESSALLY, ESMAIL; AKBARZADEH, MAGHSOD (Asian Journal of Chemistry, 2010)
The use of herbicides has intensively increased mainly due to their massive pollution of the soil and environment. As these herbicides are directly or indirectly toxic to a wide range of organisms, their potential for contaminating soil, surface water and groundwater makes these xenobiotics of special interest from a health and environmental point of view. In this work, the sum of total energy (ET), NBO charge on atoms, dipole moment, differences between HOMO and LUMO and geometrical parameters are calculated for difenoxuron (Dif), diuron (Diu), linuron (L) and metoxuron (M), at B3LYP/6-311++G (3df,2p) level of theory. Among these herbicides, linuron (L) is more effective and powerful, whereas metoxuron is the least effective herbicide. The highest HOMOLUMO gap for L shows their high stability among these herbicides.